2010
DOI: 10.1007/s12011-010-8642-0
|View full text |Cite
|
Sign up to set email alerts
|

Cell Wall Accumulation of Cu Ions and Modulation of Lignifying Enzymes in Primary Leaves of Bean Seedlings Exposed to Excess Copper

Abstract: Copper is both a nutrient and an environmental toxin that is taken up by plants. In order to determine the subcellular localization of copper and to assess the resulting metabolic changes, we exposed 14-day-old bean seedlings to nutrient solutions containing varying concentrations of Cu(2+) ions for 3 days. Biochemical analyses revealed that the cell wall was the major site of Cu(2+) accumulation in the leaves of treated plants. Excess copper modified the activity of lignifying peroxidases in both soluble and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
28
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 43 publications
(58 reference statements)
1
28
0
Order By: Relevance
“…This is consistent with the results shown in this study. It has been shown that cell wall lignification occurs in plants with copper stress [37]. Additionally, there is a relationship between the accumulation of copper in the cell wall and the responses of lignifying enzymes such as phenylalanine ammonia lyase (PAL).…”
Section: Fruit Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with the results shown in this study. It has been shown that cell wall lignification occurs in plants with copper stress [37]. Additionally, there is a relationship between the accumulation of copper in the cell wall and the responses of lignifying enzymes such as phenylalanine ammonia lyase (PAL).…”
Section: Fruit Qualitymentioning
confidence: 99%
“…Additionally, there is a relationship between the accumulation of copper in the cell wall and the responses of lignifying enzymes such as phenylalanine ammonia lyase (PAL). This response catalyzes the transformation of L-phenylalanine to cinnamic acid, which is the first step of the phenylpropanoid pathway leading to the synthesis of lignin [37,38]. Nair and Chung [14] observed root lignification when CuO NPs were applied, and mentioned that NPs could have translocated through the vascular tissues, and their subsequent dissolution to Cu ions could have given rise to the observed lignification.…”
Section: Fruit Qualitymentioning
confidence: 99%
“…Cu has emerged as a major environmental pollutant in the past few decades because of its excessive use in manufacturing and agricultural industries (Bouazizi et al, 2011). Cu build-up in the food chain has resulted in reports of Cu toxicity in humans due to the consumption of Cu-ladened food commodities (Chary et al, 2008; Desai and Kaler, 2008; Bouazizi et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Cu build-up in the food chain has resulted in reports of Cu toxicity in humans due to the consumption of Cu-ladened food commodities (Chary et al, 2008; Desai and Kaler, 2008; Bouazizi et al, 2011). Radish ( Raphanus sativus L.) tubers, which represent a rich source of antidiabetics, antioxidants, and multipotent chemopreventive factors, are particularly prone to the toxic effects of high levels of Cu, resulting in a reduction in biomass and a detrimental impact on its nutritional profile (Baek et al, 2008; Sfaxi-Bousbih et al, 2010; Sun et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…As vacuoles were included in the soluble fraction, these results seem 387 consistent with the common response of plants to toxic metals. In bean (Phaseolus vulgaris L.) 388 leaves, the cell wall was the major site of Cu ion accumulation(Bouazizi et al, 2011). Similarly, 389 root cells of Bechmeria nivea (L.) Gaud.…”
mentioning
confidence: 99%